Safety and efficacy of underwater endoscopic mucosal resection for non-pedunculated colorectal polyps larger than 10 mm - Benites-Goñi, Harold (2025)
Introduction: Colorectal cancer (CRC) is one of the leading causes of cancer-related death in Peru. Endoscopic resection of colorectal polyps has been shown to reduce the incidence and mortality of CRC. Underwater endoscopic mucosal resection (UEMR) has emerged as a safe and effective technique for the management of non-pedunculated polyps. Objectives: To evaluate the efficacy and safety of UEMR for non-pedunculated colorectal polyps larger than 10 mm in a high-complexity hospital in Lima, Peru. Materials and methods: Observational, retrospective, and descriptive study of patients aged ≥18 years who underwent UEMR between January and December 2023. En bloc resection, R0 resection, recurrence, and complication rates were analyzed. Clinical, endoscopic, and histopathological data were collected. Results: A total of 119 UEMRs were performed in 91 patients, with a median age of 72 years. 60.5% of lesions were located in the right colon, and most measured between 10–19 mm. The en bloc resection rate was 80%, and the R0 resection rate was 78%. The complication rate was 15%, including one perforation and two delayed bleeding events. Most complications occurred in the right colon. Recurrence was 3.1%, observed only in piecemeal resections. Histopathological findings included low-grade (47.9%) and high-grade (28.6%) adenomas, as well as 7 carcinomas (5.8%). Conclusions: UEMR is an effective and safe technique for the treatment of non-pedunculated colorectal polyps larger than 10 mm, particularly for lesions ≤20 mm. Its advantages include a high en bloc resection rate, low complication risk, and low cost.